دراسة العلاقة بين درجةِ الضمورِ الزغابي و كلٍّ من شدّة التظاهرات السريرية ومستوى ارتفاع قيمة Anti- tissue transglutaminase IgA عند مرضى الداء الزُلاقي البالغين - انطانيوس, ميلاد; يازجي, هيثم; عوض, رفيق (Latakia University Journal -Medical Sciences Series, 2017)
الداء الزلاقي هو مرض مناعي ذاتي تحدث فيه استجابة مناعية غير ملائمة تجاه الغلوتين تؤدي الى تأثيرات هضمية و جهازية مختلفة . للداء الزلاقي 4 أنماط ( الكلاسيكي ، اللانمطي ، الصامت ، الكامن ).ان تشخيص المرض يتم عبر الربط بين القصة المرضية و الفحص السريري مع الاختبارات المصلية ونتائج التنظير العلوي و الخزعات المتعددة من العفج .تم اجراء هذه البحث لدراسة العلاقة بين anti-tTG IgA و شدة التغيرات النسيجية بالخزعة و من أجل دراسة العلاقة بين شدة التظاهرات السريرية و درجة الضمور الزغابي .أجريت دراسة للمرضى البالغين المراجعين لمشفى الأسد و تشرين الجامعيين مابين عامي 2015 و 2016 ، حيث أجري لهم أضداد anti-tTG نمط IgA وعندما كانت النتائج إيجابية أجرينا للمرضى تنظير هضمي علوي مع خزعات عفج و تم تشخيص الداء الزلاقي اعتمادا على إيجابية الأضداد و وجود خزعة عفج Marsh ≥ 2 . النتائج : 79 مريضا كانت لديهم أضداد TTg IgA إيجابية و هؤلاء تم اجراء خزعات عفج لديهم و تم تشخيص الداء الزلاقي لدى 71 مريضا منهم أي بلغت نسبة الداء الزلاقي في مجموعة الدراسة 89.873 % ، وجدنا أنه لا يوجد ارتباط بين رقم الأضداد و الجنس أو العمر ، تنوعت التظاهرات السريرية و كان أكثرها شيوعا فقر دم بعوز الحديد (49.3 %) و ثم الألم البطني (39.4%) ، وجدنا بالدراسة أنه لايوجد علاقة بين قيم anti-tTG IgA و بين شدة التظاهرات السريرية أو القيم المخبرية و بأنه أيضا لا علاقة بين درجة الأذية النسيجية و بين شدة التظاهرات السريرية ، بينما لوحظ ترقي الأذية النسيجية بازدياد قيم anti-tTG IgA .و استطعنا تحديد قيمة ل Anti TTg IgA مشخصة للداء الزلاقي دون الحاجة لخزعات العفج بحساسية 80.3 % و نوعية تعادل 100 % و هذه القيمة هي ( الرقم الأعلى للطبيعي مضروب ب 11.35 ) . و توصلنا الى أن الاعتلال المعوي الخفيف في الداء الزلاقي هو مشكلة جدية تتطلب الالتزام الصارم بحمية خالية الغلوتين منعا من اختلاطات هذا الداء و مضاعفاته .Celiac disease is a condition in which the immune system responds abnormally to a protein called gluten , and leads to many gastrointestinal and systemic effects . There are four categories of celiac disease : (classical, atypical, silent and latent) . The diagnosis of celiac disease is established by a combination of the history , physical examination , serological tests , upper endoscopy results and multiple biopsies of the duodenum .This research is designed to study the correlation between the titres of Anti TTg IgA and between the severity of histological changes in the biopsy , and to study the correlation between the severity of clinical manifestations and between the degree of villous atrophy . The study included the adult patients who presented to Al-Assad University Hospital and Tishreen University Hospital during the period 2015- 2016 . We measured Anti tTG IgA titers . when the results were positive, patients went to upper endoscopy with duodenal biopsies . The diagnosis of celiac disease was made on the base of positive antibodies and the presence of duodenal biopsy of Marsh ≥ 2 . The results : 79 patients had positive IgA Anti tTG , and they had duodenal biopsies , the diagnosis of celiac disease was made in 71 of them . The celiac disease was found in % 89.873 of the study group .We found no correlation between the titers of Anti TTg IgA and between sex or age. The clinical manifestations varied , iron deficiency anemia was the most common (%49.3) and abdominal pain (%39.4) . Also, we found no correlation between the titers of Anti tTG IgA and between the severity of clinical manifestations or laboratory results . There was no correlation between the degree of histological damage and between the severity of clinical manifestations . We noticed that histological injury had progressed whenever the titers of Anti tTG IgA had raised . We were able to determine the titer of Anti tTG IgA in which it was diagnostic for celiac disease without the need for duodenal biopsies with sensitivity of 80.3% and specificity equivalent to 100% and this titer was : (the upper limit of the laboratory's normal serum value multiplied by 11.35). We have reached that mild enteropathy in celiac disease is a serious problem that requires strict adherence to a free gluten diet in order to prevent from the complications of the disease .